PROCYCLICALITY AND BANK LENDING BEHAVIOR IN INDONESIA: THE CASE OF DUAL BANKING SYSTEM - Zulkhibri, Muhamed; Sakti, Muhammad Rizky Prima (Bank Indonesia, 2018)
It is widely suggested in the literature that procyclicality of bank lending behavior may lead to financial instability. This study examines bank-lending channel over the business cycle for Indonesian dual banking system by ascertaining to what extent Islamic banks have a role in the credit smoothing. In this context, we utilize Indonesian dual banking system unbalanced panel data for the period 2001-2015. By employing two-step dynamic GMM estimators, the study shows that the bank lending behaviour are procyclical. However, when we categorize the lending behaviour into conventional and Islamic banks, the cyclicality of bank lending affects only for conventional banks. As for the Islamic banks, the business cycle does not affect their financing decision. Specifically, large Islamic banks are more counter-cyclical in their financing behavior than small and medium size Islamic banks. Robustness tests using different measures of loans and model specifications confirm the results that Islamic bank is more stable and less procyclical in the case of Indonesia banking system.